Semantics and legal interpretation: an approach from a comparative study of the value of embryonic life under the Argentine and U.S. constitutional case law - Zambrano, María del Pilar; Sacristán, Estela B. (Revista de Investigações Constitucionais, 2014)
The paper analyzes the issue of legal interpretation of the Constitution in the light of a comparative approach between the case law of Argentina and the United States about the value attributed to embryonic life.